Cancer-related fatigue shows a stable association with diurnal cortisol dysregulation in breast cancer patients - Schmidt, Martina; Semik, Johanna; Habermann, Nina; Wiskemann, Joachim; Ulrich, Cornelia; Steindorf, Karen (Brain, behavior and immunity, 2016)
Fatigue is a major burden for breast cancer patients undergoing adjuvant therapy. Yet, its pathophysiology is still not well understood. Hypothesized mechanisms include dysregulations in the hypothalamic-pituitary-adrenal (HPA) axis, which may be reflected in alterations in the diurnal cortisol patterns. However, studies on the association between cortisol and fatigue during adjuvant cancer therapy are rare.